The ultimate guide to video game writing and design - Dille, Flint, ....-; Platten, John Zuur, ....- (New York : Lone Eagle, 2007)
The Ultimate Guide to Video Game Writing and Design goes way beyond the basics. The authors, top game designers, focus on creating games that are an involving, emotional experience for the gamer. Topics include integrating story into the game, writing the game script, putting together the game bible, creating the design document, and working on original intellectual property versus working with licenses. Finally, there's complete information on how to present a visionary new idea to developers and publishers. Got game? Get The Ultimate Guide to Video Game Writing and Design!
Keywords: Videospelen